2013
DOI: 10.1208/s12249-013-9962-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of EDTA, Sorbic Acid, and Diclofenac Sodium in Pharmaceutical Preparations Using High-Performance Liquid Chromatography

Abstract: Abstract. A simple high-performance liquid chromatographic method for simultaneous determination of ethylenediaminetetraacetic acid (EDTA), sorbic acid, and diclofenac sodium was developed and validated. Separation was achieved on a C 18 column (10 cm×4.6 mm) using gradient elution. The mobile phase consisted of acetonitrile-ammonium dihydrogen phosphate buffer solution (0.01 M, pH02.5, containing 0.8% tetra-n-butyl ammonium hydroxide). The detector wavelength was set at 254 nm. Under these conditions, separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The determination of EDTA by ion-pairing HPLC using metallocomplexes has been known for some time [4] , [6] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] . In addition, the determination of EDTA in pharmaceutical formulations based on HPLC has been reported [5] , [20] , [21] , [23] . The use of metallocomplexes with ion-pairing chromatography introduces additional variables that require greater investigation during method development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of EDTA by ion-pairing HPLC using metallocomplexes has been known for some time [4] , [6] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] . In addition, the determination of EDTA in pharmaceutical formulations based on HPLC has been reported [5] , [20] , [21] , [23] . The use of metallocomplexes with ion-pairing chromatography introduces additional variables that require greater investigation during method development.…”
Section: Resultsmentioning
confidence: 99%
“…Laamanen et al [14] reported simultaneous determination of DTPA, EDTA and NTA by a CE/UV method using copper (II) complexation. A number of articles reported determination of trace level of APCAs in natural water, food and environmental samples by using ion-pairing reversed-phase HPLC coupled with UV-visible detector for quantitation of APCA metellocomplexes [4] , [6] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Hence, diclofenac sodium and moxifloxacin ophthalmic solutions are used simultaneously after the cataract surgery. Several analytical methods such as spectrophotometry, [8][9][10][11][12] RP-HPLC [13][14][15][16][17][18][19][20][21][22][23] and electroanalytical methods [24][25][26] were reported in the literature for the quantification of DCL and MOX alone or with other drugs. However, the simultaneous determination of DCL and MOX has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Heydari et al. developed a HPLC method for the simultaneous separation and quantitation of EDTA, sorbic acid, and diclofenac in ophthalmic solutions. Krasikovet al.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC has proven to be effective in separating and detecting various analytes [15][16][17]. Heydari et al [18] developed a HPLC method for the simultaneous separation and quantitation of EDTA, sorbic acid, and diclofenac in ophthalmic solutions. Krasikovet al [19] used HPLC-TLC to investigate the influence of molecular and structural characteristics of polyamic acids (PAAs) on their ability to form metal-polymer complexes with copper (I) chloride.…”
Section: Introductionmentioning
confidence: 99%